Sharia supervisory board and social performance of Indonesian Islamic banks - Peni Nugraheni (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2018)
This study aims to examine the effect of Sharia Supervisory Board (SSB) characteristics on the level of social performance in Islamic banks in Indonesia. Social function becomes a special feature of Islamic banks that differentiates them from conventional banks. SSB characteristics consist of size, number of meeting, educational qualification, reputation, and cross-membership of SSB members. The data is taken from annual report of Islamic banks in Indonesia for the year 2010-2014 and processed by panel data regression using eviews. The results show that size and reputation of SSB members have significant effect on the social performance while the meeting, educational qualification, and cross membership of SSB members do not have effect on the social performance. The finding also shows that social performance of IBs in Indonesia is relatively high. This study has contribution on the measurement of social performance of Islamic banks and understanding the influence of SSB characteristic on social performance of IBs in Indonesia.